Identifying the dynamic processes of the interphase short-circuit current of a wind turbine generator operating in standalone mode - Nurmaganbetova, Gulim; Kaverin, Vladimir; Issenov, Sultanbek; Em, Gennady; Ualiyev, Yerlan; Sarsembiyeva, Elmira; Nurmaganbetova, Zhanara; Issenov, Zhanat (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the electromechanical part of a wind turbine with a horizontally arranged gearless rotor and an AC generator with a capacity of up to 40 kW. The study solves the problem of analyzing the electromechanical processes that occur during an interphase short circuit in a wind turbine generator. The article presents the results of theoretical studies of the short-circuit mode of the power circuit of an AC generator of a gearless type wind turbine with a capacity of up to 40 kW. The relevance of the study is due to the need to increase reliability and reduce accidents caused by interphase short circuits in wind turbines. The choice of equations for the mathematical model of the electromechanical part of the turbine is justified; a simulation model was developed using the MATLAB package; the adequacy of the simulation model was assessed by comparing transient processes obtained theoretically and experimentally on a laboratory bench under similar initial conditions and the moments of inertia of the mechanical part of the rotating elements of the wind turbine rotor and generator; a theoretical study of transient processes during interphase short circuits has been performed. Distinctive features: the proposed energy discharge equation and the developed model allow for the estimation of the energy characteristics of a wind turbine, taking into account the dynamic characteristics of the rotor and the generator, which increases the accuracy of the analysis of the energy characteristics in the mode of interphase short-circuit of the stator windings of the generator. Practical significance: the research results can be used in the design, modernization, and adjustment of protection systems for wind turbine generators with a capacity of up to 40 kW